A new approach towards the synthesis of nitrogen-doped graphene/MnO2 hybrids for ultralong cycle-life lithium ion batteries1. Issue 12 (28th March 2015) - Yang, Tingzhou; Qian, Tao; Wang, Mengfan; Liu, Jie; Zhou, Jinqiu; Sun, Zhouzhou; Chen, Muzi; Yan, Chenglin
<x xml:space="preserve">Abstract</x> We report ultralong cycle-life lithium ion batteries based on nitrogen-doped graphene/MnO2 hybrids.